The concept of SDG-sensitive development cooperation: implications for OECD-DAC members - Alexandra Rudolph (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Since September 2015, the world has had a sustainable development agenda. The 2030 Agenda for Sustainable Development goes beyond a traditional development agenda and represents a multidimensional approach to development, with development cooperation central to the implementation of the values of the Agenda and the 17 Sustainable Development Goals (SDGs). This paper addresses the question of how to shape SDG-sensitive development cooperation in line with the requirements of the 2030 Agenda. The agenda does not extend the discussion on the role of development cooperation and ODA beyond debates of the last decades, and again pushes providers to reach at least a share of 0.7 per cent of their gross national income in ODA, target least developed countries (LDCs) and vulnerable contexts more explicitly, and mobilise additional (domestic and private) financial resources through ODA provision. The paper analyses the agenda in detail and distils the basic principles (universality and indivisibility) in order to recommend how development cooperation might be adjusted to support the implementation of the 2030 Agenda in partner countries (SDG-sensitive development cooperation). Three main messages come out of this analysis: The basic principles of the 2030 Agenda offer the possibility of reaching a coherent international policy approach for sustainable development through a “whole-of-government approach” with a strong focus on development cooperation. A comparison of the determinants of the processes for allocating ODA with the principles of the 2030 Agenda and the requirements for ODA shows leverage points where providers (members of the Development Assistance Committee (DAC) of the Organisation for Economic Cooperation and Development (OECD)) should adjust their allocation decisions (aid channel, country, sector, and instrument-mix) to provide SDG-sensitive development cooperation. Since providers' motivation in development cooperation is based primarily on strategic considerations, they should recognise the 2030 Agenda as an opportunity to use development cooperation as a strategic investment in sustainable development in partner countries, which will ultimately support sustainable development in their own countries.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Agenda 2030